2022
DOI: 10.1186/s40168-022-01384-y
|View full text |Cite
|
Sign up to set email alerts
|

Viral community-wide auxiliary metabolic genes differ by lifestyles, habitats, and hosts

Abstract: Background Viral-encoded auxiliary metabolic genes (AMGs) are important toolkits for modulating their hosts’ metabolisms and the microbial-driven biogeochemical cycles. Although the functions of AMGs have been extensively reported in numerous environments, we still know little about the drivers that shape the viral community-wide AMG compositions in natural ecosystems. Exploring the drivers of viral community-wide AMG compositions is critical for a deeper understanding of the complex interplays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 110 publications
6
59
1
Order By: Relevance
“…Interestingly, although individual AMG genes in the River Erpe were unique across compartments (27%), their functional categories were highly similar (69%) (Figure 6B). Our finding is different to a study recently reported form an estuary, where significant partitioning of AMG functions was reported between habitat types (water particle and sediment) (Luo et al, 2022). It is possible that due to the constant mixing of surface and HZ water in rivers, stratification at the genomic potential may be less notable, and expression information may be necessary to capture habitat specific differences.…”
Section: Viruses Have the Potential To Regulate River Biogeochemical ...contrasting
confidence: 99%
“…Interestingly, although individual AMG genes in the River Erpe were unique across compartments (27%), their functional categories were highly similar (69%) (Figure 6B). Our finding is different to a study recently reported form an estuary, where significant partitioning of AMG functions was reported between habitat types (water particle and sediment) (Luo et al, 2022). It is possible that due to the constant mixing of surface and HZ water in rivers, stratification at the genomic potential may be less notable, and expression information may be necessary to capture habitat specific differences.…”
Section: Viruses Have the Potential To Regulate River Biogeochemical ...contrasting
confidence: 99%
“…Of the 953 bacterial MAGs with a predicted phage, particularly many phage-host interactions were identified involving MAGs classified as Rubrivirax (n=49), Novosphingobium (n=38), Rhizobacter (n=38), Aquabacterium (n=33) and Polaromonas (n=33)(Figure 3e). Similar to other work (Luo et al, 2022), the majority of phage-host interactions (84.2%) involved a single phage-host pair and only 6 phages had more than 10 predicted interactions with different MAGs (maxinteractions = 13). In line with generally high host specificity, vMAGs with multiple host interactions tended to interact with taxonomically similar MAGs (Figure 3e,f).…”
Section: Resultssupporting
confidence: 84%
“…Phages could compensate for bacterial adaptability and exhibited specific patterns in habitat patterns facing different environmental stresses. 93 The pAMGs related to energy metabolism might enhance nutrient utilization and thus fitness advantages for bacterial hosts in SMA. The pAMGs related to the biosynthesis of antioxidants could confer tolerance of bacterial hosts to oxidative stress in AMA (e.g., membrane cleaning chemicals).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phages could compensate for bacterial adaptability and exhibited specific patterns in habitat patterns facing different environmental stresses . The pAMGs related to energy metabolism might enhance nutrient utilization and thus fitness advantages for bacterial hosts in SMA.…”
Section: Resultsmentioning
confidence: 99%